Regulations and Recommendations for Appropriate Disposal of Antineoplastics - Pedro, Elsa; Lugo-Rosado, Idaliz; Rojas-Brenes, María (Puerto Rico Health Sciences Journal, 2010)
Properly disposing of antineoplastics is crucial for protecting the environment and the health of the employees who dispose of them. Despite of the evidence-based scientific recommendations and federal regulations for the appropriate disposal of hazardous drugs including antineoplastics, some institutions in Puerto Rico still do not implement them. Some companies dealing with the disposal of these products do not meet the established regulations and some health-care institutions still do not dispose of the antineoplastics in their correct containers. This situation significantly impacts on the disposal process of these toxic wastes and has the potential to become a health threat in Puerto Rico. The list of drugs classified as hazardous drugs (including antineoplastics) by the Environmental Protection Agency has not been updated since 1976. Therefore, there are many new antineoplastics that have not been included in this list. However, there are agencies that make recommendations based on scientific evidence taking in consideration the emergence of these new drugs. The implementation of these regulations and recommendations in the work setting are essential to avoid exposing employees and the environment to this hazardous waste.